Goliatmusseron (Tricholoma matsutake) - Risberg, Lotta (2007)
Modern forestry management may disadvantage some mykorrhiza forming fungi because; they are dependent on late successions and cannot survive the constantly recurring breaks in the continuity of their host tree. For this study the specie goliatmusseron (Tricholoma matsutake) was chosen to investigate this possibility. In Sweden T. matsutake is found in greatest amounts north of Örnsköldsvik on glacifluvial sandy soils in association with pine trees and reindeer lichens.